Proses Berpikir Kritis Siswa SMP dalam Menyelesaikan Masalah Aljabar Ditinjau dari Gaya Kognitif Reflektif-Impulsif - Irfana, Nahda; Ismail, Ismail (Universitas Negeri Surabaya, 2024)
Efforts that can be made to achieve educational targets in the 21st century require an individual to have at least one of the four main abilities known as the 4Cs, namely critical thinking in analyzing and solving problems. Steps that can be used by teachers to improve critical thinking are posing problems. Algebra is material related to mathematical problems. Every student's critical thinking process is different, this is related to cognitive style. One cognitive style is reflective-impulsive. This descriptive-qualitative research aims to describe the critical thinking process of 3 students in completing algebra material in terms of their reflective-impulsive cognitive style. The instruments used in this research were researchers, MFFT and Algebraic Critical Thinking Process Tasks. Critical thinking process data was analyzed based on Jacob and Sam's stages and interview results were analyzed based on Miles, Hubberman and Sam, namely data condensation, data presentation and conclusion drawing. The results of this research show that (1) reflective students demonstrate three stages maximally, namely clarification, assessment, and inference stage. However, at the strategy stage there are indicators that reflective students do not show, namely discussing problem solving steps that might be implemented. (2) impulsive students show two stages of critical thinking, namely the clarification stage and the assessment stage, while at the strategy and inference stages there are indicators that impulsive students do not show. At the strategy stage students do not use other solution plans and do not check again. At the inference stage, students were less than optimal in the indicators of establishing relationships between different parts of the problem. The results of this research can be used as reference material for designing students' critical thinking process assignments in algebra material. Keywords: Critical Thinking Process, Problem Solving, Reflective-Impulsive